Efficacy of nirsevimab for the prevention of RSV disease in infants: A systematic review, meta-analysis of randomized controlled trials, and global perspectives on recommendations and unmet needs - Lien, Hsin-Chweng; Lien, Chi-Hone; Liu, Tzu-Yu; Weng, Shun-Long; Tai, Yu-Lin; Huang, Ya-Ning; Chi, Hsin; Chiu, Nan-Chang; Yeung, Chun-Yan; Lin, Chien-Yu (Pediatrics and neonatology, 2025)
Respiratory syncytial virus (RSV) is a major cause of infant hospitalizations, with limited prophylactic options historically available. Nirsevimab, a long-acting monoclonal antibody, has emerged as a promising agent for preventing RSV. To evaluate the efficacy and safety of nirsevimab through a systematic review and meta-analysis of randomized controlled trials (RCTs) and investigate current global recommendations. Databases, including PubMed, Embase, and Cochrane CENTRAL, were searched from inception to January 31, 2025. Eligible RCTs assessing nirsevimab efficacy in RSV prevention were included. Outcomes encompassed RSV-related hospitalization, severe infection, and adverse events. Meta-analysis employed random-effects models. Six RCTs (n = 12,086) were included. Nirsevimab significantly reduced RSV-related hospitalization (odds ratio [OR], 0.19; 95 % confidence interval [CI], 0.13–0.30) and severe RSV infection (OR, 0.23; 95 % CI, 0.12–0.44), with no increase in adverse events. Country-specific recommendations varied, ranging from seasonal to year-round strategies. Nirsevimab exhibits excellent efficacy and safety in RSV prevention. Although most countries align administration with RSV seasonality, Taiwan distinctively endorses year-round prophylaxis. Customized immunization policies considering local epidemiology and seasonality may optimize protection and inform global RSV prevention strategies.